(untitled) (Bulletin of Innovative Research, 2026)
This article analyzes contemporary trends in the creative practices of folk comic performers, the factors influencing their formation, and their artistic and aesthetic features. In particular, it examines the transformation of traditional comic performance under the influence of current socio-cultural processes, including changes in stage interpretation, the expansion of thematic scope, and innovations in performance techniques. Furthermore, the study systematizes the prospective creative directions of future folk comic performers, classifies the principles of repertoire formation, explores the techniques of character construction, and analyzes the mechanisms of establishing communicative interaction with audiences. The article also presents scholarly conclusions and practical recommendations regarding the future development of this art form.